Maktabah Hadits/Historiografi Hadits (Munculnya Kutub al-Sittah dan Sistematika Penyusunannya) - Rohman, Teguh Abdul; Mighwar, Muhammad al (Asian Journal of Islamic Studies and Da'wah, 2024)
To save hadiths from corruptive and misleading "blemishes," scholars have worked extraordinarily hard in compiling hadiths, developing various knowledge, and creating principles and methods for hadith writing and research. The Kutubu Sittah refers to the six hadith books that have become references for subsequent scholars. The study related to the Kutubu Sittah is crucial, considering that many hadith enthusiasts only focus on the texts contained within these collections without delving into who the authors were and what their writing methodologies were. The research includes several primary reference books such as Kutubu Sittah, al-Hadith wal-Muhaddithun, Fii Rihab as-Sunnah al-Kutub as-Sihhah, Atlas Hadith an-Nabawiyyah, and others, utilizing a library research approach. The existence of these six hadith books in the hands of Muslims today is tangible evidence of how Allah has preserved the Sunnah and the scholars. Although these scholars are noble, they are not free from mistakes, and thus, in compiling these books, some errors were inevitable. However, even though some hadiths are considered weak by some scholars, their nobility will never diminish.